Planting Moral Values in Youth Victims of Broken Home Through Family Guidance (Case Study in Ma'had Intensive Putri Institute of Dirosat Islamiyah Al-Amien Prenduan) - Alfira Aghnia (Penerbit Hellow Pustaka, 2024)
Moral values ​​are a measure of a person's attitudes and behavior, which can be measured from good or bad, right or wrong. A person will be said to be moral when in his behavior he has good ethics and does not violate the norms that apply in his environment. Of course, behavior cannot be arbitrary and careless, there must still be a measure in every attitude we carry out because basically morals are the benchmark for our behavior in society. Broken home is where the family cannot be reunited or is called divorce. This divorce is where the parents no longer care about the messy home situation which can cause children to have problems both at home, at school and in the community. Family guidance is an approach that can be used by counselors to provide assistance to a family through interactions between members so that the family can overcome the problems it faces for the overall welfare of family members with the aim of achieving a harmonious family. In this research, the problem examined is how family guidance is in instilling moral values ​​in adolescent victims of broken homes, and what are the implications of these moral values ​​for the lives of adolescent victims of broken homes and the aim of this research is to find out how family guidance is in instilling moral values ​​towards teenage victims of broken homes and what are the implications of these moral values ​​for the lives of teenage victims of broken homes. This research uses qualitative research methods, qualitative research is observing people in the environment, interacting with them and interpreting their opinions regarding the world around them. This type of research is case study research. Based on the description presented by the researcher, a conclusion can be drawn, family guidance in instilling moral values ​​in young people who are victims of broken homes, running well, increasing children's spirituality, providing positive knowledge, teaching self-adjustment. The implications of these moral values ​​for the lives of teenagers who are victims of broken homes through a family guidance approach have a very good impact on teenagers, in forming good character and having the skills to make good decisions.